Sex differences in the distribution and density of regulatory interneurons in the striatum - Van Zandt, Meghan; Flanagan, Deirdre; Pittenger, Christopher (Frontiers in Cellular Neuroscience, 2024)
Dysfunction of the cortico-basal circuitry -including its primary input nucleus, the striatumcontributes to neuropsychiatric disorders, such as autism and Tourette Syndrome (TS). These conditions show marked sex differences, occurring more often in males than in females. Regulatory interneurons, such as cholinergic interneurons (CINs) and parvalbumin-expressing GABAergic fast spiking interneurons (FSIs), are implicated in human neuropsychiatric disorders such as TS, and ablation of these interneurons produces relevant behavioral pathology in male mice, but not in females.Here we investigate sex differences in the density and distribution of striatal interneurons, using stereological quantification of CINs, FSIs, and somatostatin-expressing (SOM) GABAergic interneurons in the dorsal striatum (caudate-putamen) and the ventral striatum (nucleus accumbens) in male and female mice. Males have a higher density of CINs than females, especially in the dorsal striatum; females have equal distribution between dorsal and ventral striatum. FSIs showed similar distributions, with a greater dorsal-ventral density gradient in males than in females. SOM interneurons were denser in the ventral than in the dorsal striatum, with no sex differences. These sex differences in the density and distribution of FSIs and CINs may contribute to sex differences in basal ganglia function, particularly in the context of psychopathology.